Sigmoid pid based adaptive safe experimentation dynamics algorithm of portable duodopa pump for parkinson’s disease patients - Razak Ramesh, N. H. A.; Ghazali, M. R.; Ahmad, M. A. (IAES, 2021)
This paper emphasizes on the development of an appropriate closed-loop control strategy for traditional portable duodopa pump (PDP); thereby ensuring an automated drug infusion without wearing off. In particular, a sigmoid proportional integral derivative (SPID) controller is adopted to control the blood plasma level of dopamine. The parameters of SPID controller are tuned using the adaptive safe experimentation dynamics (ASED) algorithm. The efficiency of the suggested SPID-ASED is evaluated by concerning the convergence plot of the cost function, the amount of dopamine in the blood plasma (BP) of the patient, the statistical analysis of cost function, norm of error and norm of input, and time responses specifications. The simulation results show that the proposed SPID-ASED outperforms the standard PID controller in terms of better control accuracy with minimum overshoot and settling time.